Passes through (-6,5) and parallel to 2x-3y=12

Answers

Answer 1
Answer: Steps:
1. Do the point slope form
Y-Y1=m(x-x1)
Y-5=2(x + 6)
Y-5=2x +12
2. Now you add 5 to the number 12
3. Your answer is
Y=2x +17

Related Questions

The distance in meters of a basket suspended on a spring to a tabletop below is dependent on the number of steel bearings in the basket. The function representing this relationship is d(m) = 7 – 2m, where d(m) represents the distance in meters, and m represents the number of steel bearings in the basket. Which set represents the evaluation of the function d(m) = 7 – 2m when m ∈ {0, 1, 2, 3}?
Examine this expanded form.1(a)(a)(a)(a)(a)(a)Which is the expression in exponential form?
Is the equation always sometimes or never true . . 15+2x-4=9x+11-7x. . 2x+3(4x-1)=2(5x+3)+4x
What would a model be for the math word problem Sammy has 50 pieces of gum. He wants to give 1/2 of the pieces to his brother and 3/4 of the pieces to his sister.
Money off coupons have been circulated to 300 households. Only 2/5 of these were redeemed (used) in the local supermarket to get a free shampoo. What fraction of the coupons were unused ?

Use Synthetic Division to Factor the following polynomials completely by given factors or roots and Find all the zeros; When you reach quadratic equation, performance regular factoring or Quadratic Formula. x^(5) -9x^(3) -x^(2)   +9;(x-3),(x-1), as factors and -3 as a root

Answers

Answer:

The factors are (x - (1 - i√3)/2) , (x - (1 + i√3)/2) , (x - 3) , (x + 3) , (x - 1)

The zeroes are 1 , 3 , -3 , (1 - i√3)/2 , (1 + i√3)/2

Step-by-step explanation:

(x^(5)+0-9x^(3) -x^(2)+0+9) ÷ (x - 3) =

(x^(4)-9x^(3)-x^(2)+0+9) ÷ (x - 3) =

x^(4)+3x^(3)+(-x^(2)+0+9) ÷ (x - 3) =

x^(4)+3x^(3)-x+(-3x+9) ÷ (x - 3) =

(x^(4)+3x^(3)-x-3)

(x^(4)+3x^(3)+0-x-3) ÷ (x - 1) =

x³ + (4x³ + 0 - x - 3) ÷ (x - 1) =

x³ + 4x² + (4x² - x - 3) ÷ (x - 1) =

x³ + 4x² + 4x + (3x - 3) ÷ (x - 1) =

x³ + 4x² + 4x + 3

∵ -3 is a root ⇒ (x + 3) is a factor

(x³ + 4x² + 4x + 3) ÷ (x + 3) =

x² + (x² + 4x + 3) ÷ (x + 3) =

x² + x + (x + 3) ÷ (x + 3) =

x² + x + 1 ⇒ use the formula to find the factors of this quadratic

∵ a = 1 , b = 1 and c = 1

x=\frac{-1+\sqrt{(1)^(2)-4(1)(1)} }{2(1)}=(-1+√(-3))/(2)=(-1+i√(3))/(2)

x=(-1-i√(3) )/(2)

∴ The factors are (x - (1 - i√3)/2) , (x - (1 + i√3)/2) , (x - 3) , (x + 3) , (x - 1)

The zeroes:

x - 3 = 0 ⇒ x = 3

x + 3 = 0 ⇒ x = -3

x - 1 = 0 ⇒ x = 1

x - (1 - i√3)/2 = 0 ⇒ x = (1 - i√3)/2

x - (1 + i√3)/2 = 0 ⇒ x = (1 + i√3)/2

The zeroes are 1 , 3 , -3 , (1 - i√3)/2 , (1 + i√3)/2

The sum of 6 consecutive integers is 387. what is the sixth number in this sequence?

Answers

6 consecutive integers : x, x + 1, x + 2, x + 3, x + 4, x + 5

the sum is 387...
x + x + 1 + x + 2 + x + 3 + x + 4 + x + 5 = 387...combine like terms
6x + 15 = 387
6x = 387 - 15
6x = 372
x = 372/6
x = 62

the 6th number, which is x + 5 is : 62 + 5 = 67 <==

Alex is feeling stressed this morning. He did not get enough sleep because a dog barked most of the night. The dog barked from 11;41p.m. until 12:09 a.m.Then it started barking again at 3:35 a.m. and didn’t stop until 4:10 a.m.How long did the dog bark in all?

Answers

Answer:

Poor Alex, I know how they feel, I got a dog myself.

The amount of time between

11:41 pm to 12:09 am is

19 minutes (to 12 am, 60 minutes to next hour) + 9

which is 28 minutes for the first dog barking session

the second time is 35 minutes,

using same method as before.

adding the two separte barking sessions we get

35+28= 63 minutes

which is equivelant to 1 hour and 3 minutes.

In conclusion the dog barks for 1 hour and 3 minutes in total.

PLEASE HELP. A playground is shaped like a rectangle with a width 5 times its length (l). What is a simplified expression for the distance between opposite corners of the playground?

Answers

Look at the picture.

Use the Pythagorean Teorem:
l^2+(5l)^2=d^2\nl^2+5^2l^2=d^2\nd^2=l^2+25l^2\nd^2=26l^2\nd=√(26)^2\nd=√(26)\cdot√(l^2)\n\boxed{d=l√(26)}

Solve this linear equations: x + y + z = 34 1x + 10y + 5z = 100

Answers

Answer

To solve this system of linear equations, we can use the method of substitution.

First, let's solve the first equation for x:

x = 34 - y - z

Now, we substitute this value of x into the second equation:

1(34 - y - z) + 10y + 5z = 100

34 - y - z + 10y + 5z = 100

34 + 9y + 4z = 100

Next, we simplify the second equation:

9y + 4z = 100 - 34

9y + 4z = 66

We can rewrite this equation as:

9y = 66 - 4z

y = (66 - 4z) / 9

Now, we substitute this value of y back into the first equation:

x + (66 - 4z) / 9 + z = 34

Multiplying through by 9 to eliminate the fraction:

9x + 66 - 4z + 9z = 306

9x + 5z = 240

Now we have a system of two equations in two variables:

9x + 5z = 240

9y + 4z = 66

We can solve this using the method of substitution or elimination. Let's use the method of elimination:

Multiplying the first equation by 4 and the second equation by 5, we get:

36x + 20z = 960

45y + 20z = 330

Subtracting the second equation from the first, we eliminate z:

36x - 45y = 630

We can simplify this equation by dividing through by 9:

4x - 5y = 70

Now, let's solve the new system of equations:

4x - 5y = 70

9y + 4z = 66

We can multiply the first equation by 9 and the second equation by 4 to eliminate x:

36x - 45y = 630

36y + 16z = 264

Now, subtracting the first equation from the second, we eliminate y:

36y + 16z - 36x + 45y = 264 - 630

81y + 16z = -366

Dividing through by 3, we get:

27y + 16z = -122

Now, we have a system of two equations in two variables:

4x - 5y = 70

27y + 16z = -122

We can solve this system using the method of substitution or elimination.

How to convert 25.12% into a fraction of 10,000

Answers

Answer:

25.12/100

Step-by-step explanation:

Percent means per hundred, so 25.12 percent means 25.12 per hundred. Thus, you can make 25.12 the numerator and 100 the denominator, and make 25.12 percent a fraction like this:

25.12/100